Analisis Penetapan Tarif Sewa Gedung Sikka Convention Center dan Kontribusinya dalam Meningkatkan Pendapatan Asli Daerah Kabupaten Sikka - Fransiska Fortunata Rebong; Yosefina Andia Dekrita; Yan Yanitza Salvanos (Journal Of Business, Finance, and Economics (JBFE), 2025)
This study aimed to analyze the determination of rental rates for the Sikka Convention Center (SCC) and its contribution to increasing the Local Own-Source quantitative with a descriptive approach. The property value was calculated using the Cost Approach, where the land value was obtained based on the Tax Object Sale Value (Nilai Jual Objek Pajak, NJOP) and the building value was calculated using the Income Capitalization Approach. The results showed that the property value of SCC consisted and of a constant land value and a building value that fluctuated according to annual rental income. SCC rental income experienced significant changes, peaking in 2022 and declining again in 2024. The actual contribution of SCC rental income to increasing PAD in Sikka Regency remained very small, with the highest achievement in 2022; however, it had not yet provided a significant overall impact. Meanwile, calculations pf contribution based on optimal potential showed higher values compared to the actual realization, although it was still considered low in enhancing PAD in Sikka Regency.